Implementing Authentic Assessment Strategies in Afghan ESL Classrooms - Nadir, Laila (Journal of Social Sciences - Kabul University, 2020)
Authentic assessment is widely practiced in modern educational methodologies, yet its implementation remains limited in certain regions of Afghanistan. In many remote areas, teachers continue to rely on traditional assessment methods such as mid-term and final exams, while some institutions have adopted alternative strategies to evaluate students’ progress. In the 21st century, it is essential to adopt updated teaching and assessment approaches that better support student learning. Teachers must facilitate realistic and meaningful tasks that enhance students’ engagement and skills. This research paper explores various authentic assessment tools and their benefits in the Afghan context. A review of reliable sources on the topic reinforces the idea that authentic assessment provides students with valuable opportunities to succeed both academically and in their future careers.